Profilling Sensory of Gluten-Free Almond Crispy from Pedada Fruit Flour and Mocaf Flour with the Addition of Anchovy Flour Using the Rate All That Apply (RATA) Method - Sofia Balqis Lesmana; Jariyah; Andre Yusuf Trisna Putra; Sri Winarti; Hadi Munarko (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Almond crispy is a thin, round cookie characterized by a crunchy texture and a topping of almonds and grated cheese. This study aimed to analyze the sensory profile of almond crispy made from a combination of pedada fruit flour, mocaf flour, and anchovy flour using the Rate All That Apply (RATA) method to identify consumer preferences. Nine formulations were tested with varying ratios of pedada and mocaf flours (5%, 10%, 15%) and different levels of anchovy flour (5%, 10%, 15%). Sensory evaluation involved panellist questionnaires, Focus Group Discussions (FGD), and sensory tests. Data were analyzed using Principal Component Analysis (PCA), preference mapping, and Kruskal-Wallis followed by Dunn’s test at a 5% significance level. Results indicated that samples P0T0 and P1T1 were preferred, exhibiting milky and roasted aromas, milky and sweet tastes, crunchy textures, bright colours, and dry mouthfeels. These findings provide insights into optimizing almond-crispy formulations based on consumer sensory preferences. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 12: Responsible Consumption and Production